Effect of Cryopreservation on Extracellular Matrix Proteins of Vascular Prostheses - Shevchenko, Evgeniy V.; Tynynyka, Lyudmila N.; Mikhaylova, Irina P.; Sandomirsky, Boris P.; Naumova, Olga V. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(3):262-267.